2019
DOI: 10.5650/jos.ess18148
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Plasma Octanoylated Ghrelin Levels in Mice by Oleanolic Acid

Abstract: INTRODUCTION Ghrelin is a 28-amino-acid peptide hormone initially identified in the rat stomach that acts as an endogenous ligand for the growth hormone secretagogue receptor 1. Ghrelin circulates in the blood as two main isoforms: octanoylated ghrelin and des-acyl ghrelin 2. Octanoylated ghrelin, the active form, stimulates appetite and induces body weight gain, whereas des-acyl ghrelin, which has no acyl modification, does not have these activities 3. Furthermore, octanoylated ghrelin decreases energy expend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Similarly, Gamede et al [ 96 ] have shown that OA significantly decreased body weight, TG, and LDL in plasma of prediabetic rats and significant rise of HDL. Further, OA administration lowers saturated FFA and increases mono/polyunsaturated FFA in neonatal rats fed with an HF diet [ 97 ], and significantly diminishes the plasma levels of octanoylated ghrelin and the body weight gain in comparison to non-OA-fed rats [ 98 ]. In the liver of spontaneously hypertensive rats (SHR) treated with OA (1.08 mg/kg) for 4 weeks, Zhang et al [ 99 ] observed a decrease in TG levels; however, they also found increased plasma LDL-C levels, with no significant effects on HDL-C and total cholesterol.…”
Section: Biological Activity Of Oamentioning
confidence: 99%
“…Similarly, Gamede et al [ 96 ] have shown that OA significantly decreased body weight, TG, and LDL in plasma of prediabetic rats and significant rise of HDL. Further, OA administration lowers saturated FFA and increases mono/polyunsaturated FFA in neonatal rats fed with an HF diet [ 97 ], and significantly diminishes the plasma levels of octanoylated ghrelin and the body weight gain in comparison to non-OA-fed rats [ 98 ]. In the liver of spontaneously hypertensive rats (SHR) treated with OA (1.08 mg/kg) for 4 weeks, Zhang et al [ 99 ] observed a decrease in TG levels; however, they also found increased plasma LDL-C levels, with no significant effects on HDL-C and total cholesterol.…”
Section: Biological Activity Of Oamentioning
confidence: 99%
“…Then the obese mice were intragastric administrated with vehicle, 25 mg/kg or 50 mg/kg OA for 4 weeks. The tested OA concentration was adapted from previous studies that used doses of 20, 40, 250 mg/kg/day, or 50 mg/kg/3 days in mice (Wang et al, 2015;Su et al, 2018;Nakajima et al, 2019), and 5-100 mg/kg/day in rats (Ying et al, 2014;Lee et al, 2016;Matumba et al, 2019).…”
Section: Oleanolic Acid Significantly Improves Metabolic Dysfunction In Obese Mice Induced By High-fat Dietmentioning
confidence: 99%
“…In this line, the literature supports that OA increases insulin biosynthesis and secretion [10], which is in accordance with the increased insulin levels and HOMA-β index [37], as well as the reduced FSI levels [35,36,38,43]. In addition, Li et al [33], Wang et al [35], Su et al [37], and Nyakudya et al [40] reported an improvement in the HOMA-IR index, whereas Gamede et al [41] reported an improvement of the HOMA-2 IR index. These findings might be explained by the availability of OA to modulate insulin signaling pathways such as glycogen synthase (GS)/glycogen phosphorylase (GP) signaling pathway [61,62] or the insulin receptor substrate 1 (IRS1)-glucose transporter 4 (GLUT4) pathway via NF-κB [17].…”
Section: Discussionmentioning
confidence: 67%
“…Molepo et al [12] administered OA to neonatal rats fed with a HF diet and observed a decrease of saturated FFA, and an increase of mono/polyunsaturated FFA. OA administration by Nakajima et al [41] significantly reduced the plasma levels of octanoylated ghrelin levels and the body weight gain in comparison to non-OA-fed rats.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation